Perception about central induction policy among postgraduate trainees of Punjab - a mixed method qualitative study (Journal of Fatima Jinnah Medical University, 2021)
Background: Central induction policy is recently implemented for induction of doctors for post-graduation training based on their performance in MBBS, post-graduation entrance exam, house job, studying in public institute, work in periphery and research. Despite controversies this policy was implemented in May 2016 and no feedback was taken by the stakeholders. This discrepancy aroused the need for data collection to determine effectiveness of CIP in terms of PG perceptions.Subjects and methods: An interview based qualitative study was conducted in four Tertiary care hospitals from 05 June 2018 to 30 November 2018. Request forms were randomly sent to 75 residents inducted through and before CIP. Total 39 residents participated in the study after giving consent. Interview questions were selected by the authors after detailed discussion. Each interview was heard thrice, manuscripts were prepared in the same words used by the participant. Manuscripts were discussed among the team members to identify themes. Depending upon themes questionnaire was designed and quantitative data was collected.Results: Qualitative evaluation identified following major themes including policy being merit based allowing every candidate to get a fair chance of induction; financial security on all the slots and provision of qualified doctors at primary health care centers for the induction policy whereas issues with choice of specialty and place of work, delay in start of training due to various factors and discrepancy in special cases like wedlock, FMGs, authenticity of research papers were identified as demerits.Conclusion: CIP is a good initiative and is acceptable due to its merit based policy and financial security however there is need to improve the standard and evaluation method of research and option for change of specialty.
Keywords: Central Induction Policy; Postgraduation; Training; JCAT; FCPS; Peripheral health care centres; Research